3D negative thermal expansion in orthorhombic MIL-68(In). Issue 45 (18th May 2018) - Liu, Zhanning; Li, Qiang; Zhu, He; Lin, Kun; Deng, Jinxia; Chen, Jun; Xing, Xianran
Abstract : Rare three-dimensional negative thermal expansion (NTE) has been found in a low symmetry compound, orthorhombic MIL-68(In). Abstract : Negative thermal expansion (NTE), lattice contraction upon heating, has been found in some metal organic frameworks (MOFs). To date, MOF compounds have been found to present either isotropic NTE in the cubic phase or 1D or 2D NTE in a low symmetry structure. Herein, we report anisotropic NTE in orthorhombic MIL-68(In) with the 3D NTE of α a = −5.6 × 10 −6 K −1, α b = −2.7 × 10 −6 K −1 and α c = −4.0 × 10 −6 K −1 . A synchrotron X-ray diffraction study shows that the transverse vibration of the phenyl ring leads to the NTE in the ab plane. Further high-energy synchrotron X-ray total scattering investigation reveals that the rotation of rigid octahedrons gives rise to the NTE along the c -axis. Such abnormal 3D NTE in orthorhombic MIL-68(In) is accounted for by the combination of transverse vibration and rigid unit modes. This is the first case to show 3D NTE in a low symmetry MOF compound and it will be beneficial to tailor the thermal expansion of functional MOF materials.